2020
DOI: 10.1093/mnras/staa2138
|View full text |Cite
|
Sign up to set email alerts
|

High time resolution and polarization properties of ASKAP-localized fast radio bursts

Abstract: Combining high time and frequency resolution full-polarisation spectra of Fast Radio Bursts (FRBs) with knowledge of their host galaxy properties provides an opportunity to study both the emission mechanism generating them and the impact of their propagation through their local environment, host galaxy, and the intergalactic medium. The Australian Square Kilometre Array Pathfinder (ASKAP) telescope has provided the first ensemble of bursts with this information. In this paper, we present the high time and spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
127
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(140 citation statements)
references
References 44 publications
12
127
1
Order By: Relevance
“…FRB 190611 shows time-varying polarization properties as well as an apparent change in dispersion measure between the two components (Day et al 2020). The apparent variations in dispersion measure, Faraday rotation measure, and polarization properties between the components of some FRBs (e.g., Cho et al 2020;Day et al 2020) may be interpreted as emission observed along different sightlines through a dense, magnetized, trans-relativistic plasma (Vedantham & Ravi 2019), possibly with several radial magnetic-field reversals (Gruzinov & Levin 2019). This scenario is consistent with our picture of significant spatial separations between emission sites for multiple-component FRBs.…”
Section: Extragalactic Frbssupporting
confidence: 88%
See 3 more Smart Citations
“…FRB 190611 shows time-varying polarization properties as well as an apparent change in dispersion measure between the two components (Day et al 2020). The apparent variations in dispersion measure, Faraday rotation measure, and polarization properties between the components of some FRBs (e.g., Cho et al 2020;Day et al 2020) may be interpreted as emission observed along different sightlines through a dense, magnetized, trans-relativistic plasma (Vedantham & Ravi 2019), possibly with several radial magnetic-field reversals (Gruzinov & Levin 2019). This scenario is consistent with our picture of significant spatial separations between emission sites for multiple-component FRBs.…”
Section: Extragalactic Frbssupporting
confidence: 88%
“…However, FRB 190611, a two-component burst detected by ASKAP and tentatively localized to a host galaxy at z=0.378 (Macquart et al 2020), shows qualitative similarities with the picture described here (Day et al 2020). The two components separated by ∼1 ms show evidence of scintillation from the Milky Way ISM (consistent between the two components) in addition to an overall envelope that has a central frequency 48 MHz higher for the latter component (Day et al 2020). Estimating Δν=100 MHz at 1250 MHz, assuming that the screen, as in the case of SGR 1935+2154, is 16 pc from the source, 4 and using the Planck 2015 cosmological parameters (Planck Collaboration et al 2016) to calculate the angular diameter distance to the source, we find l d =3.2×10 13 km and V src,app >160c, implying a highly relativistic emission region, with ΓV src,app /c or a separation between two emission regions of 4.7×10 7 m. Such high Lorentz factors are predicted by Beloborodov (2020) and Margalit et al (2020b) for extragalactic FRBs.…”
Section: Extragalactic Frbssupporting
confidence: 70%
See 2 more Smart Citations
“…On UT 2019 July 11 at 01:53:41.1, the ASKAP telescope recorded FRB 190711 as reported by Macquart et al (2020), who also provided a brief description of its host galaxy. The FRB position is at α, δ=21 h 57 m 40 68, −80 d 21 m 28 8 (J2000), with an uncertainty of σ α,δ =0 4, 0 3 (Day et al 2020). This FRB has subsequently been found to repeat (Kumar et al 2020).…”
Section: Frb 190711mentioning
confidence: 95%